La catastrophe de la Montagne Pelée le 8 mai 1902 en Martinique : Saint-Pierre, une ville résiliente ou un exemple archétypal de bifurcation - Fanny Benitez (Physio-Géo)
The purpose of this article is to analyse the effects of a major disaster on the territorial trajectory of a city, by combining different spatial and temporal scales. Feedback shows that, in the face of a catastrophic event, cities adopt very different recovery trajectories, which are now described through the concept of resilience. From a geohistorical perspective, the notion of resilience alone cannot explain long-term territorial trajectories. Using the example of the city of Saint-Pierre in Martinique, devastated by the eruptions of Mount Pelée in 1902, we were able to demonstrate that the city's trajectory did not correspond to a trajectory of resilience, contrary to what the actors claim. To do this, we combined archival work with a population survey in 2016. The geohistorical approach makes it possible to go beyond the discourse of the actors of the territory, which presents Saint-Pierre as a resilient city. Depending on the time step and spatial scale considered, the territorial trajectory of Saint-Pierre may take the form of a spatial reproduction with a survival of the name and site, a bearing with degradation compared to the previous situation or a fork. The geohistorical analysis of the trajectory of Saint-Pierre finally shows that there is no resilience in itself for urban territories.